Faktor-Faktor Pelaksanaan TQM dalam Industri Minyak Sawit: Kajian Kes - Ahmad @ Mohamad, Md Fauzi; Rashid, Nurulizwa; Ahmad Nur Aizat Ahmad; Abdul Latip, Hamrila (Research in Management of Technology and Business, 2023)
Total Quality Management (TQM) is a management system for a customer-focused through all employees’ participation in continuous improvement. It integrates the quality discipline into the culture and actions of the organization through strategy, data, and effective communication. Many organizations have viewed that TQM practices as an effective approach to enhance customer satisfaction as well as to gain sustainable competitive advantage. Nevertheless, there are less empirical study of TQM in palm oil industry. This study was conducted to identify the TQM adoption in rank factors based on the importance, identifying the barrier of implementing the practices, evaluating the implementation and providing proposed solutions by using SWOT analysis. In this study, ABD Sdn. Bhd has been chosen for the case study. Descriptive analysis as the central of this study whereby in-depth interview as the research instrument. In this research, “continuous improvement” was found to be the most important factors of the implementation TQM, followed by “quality assurance” and “human resource mnagement” based on their priority weights. This study is beneficial to help manufacturing companies as a guideline to improve their TQM practices.